PERAN RANTING âAISYIYAH MAKAM HAJI KARTASURO SUKOHARJO PERIODE 2010-2015 DALAM MENINGKATKAN PENDIDIKAN ISLAM DI MASYARAKAT MAKAMHAJI TAHUN 2012/2013â - Ammah, Aisyah Fitrotul (Universitas Muhammadiyah Surakarta, 2014)
This is field research with a focus on the role of Aisyiyah branch in Makamhaji Kartasuro Sukoharjo in improving Islamic education in public community, which are conclusions that: Role of Aisyiyah branch Makamhaji in improving Islamic education in society namely: (a) formal Islamic education, founded and built kindergarten school ABA Makamhaji 1, 2 and Free School Intan Permata. (B) non-formal Islamic education, founded ECD (Early Childhood Education) .. Early Childhood Education that existed at the Branch Aisyiyah Makamhaji is TPAB Intan Permata, TPQ Intan Permata and Play Group Intan Permata. Informal Islam education. (C) Â Informal Islamic Education Branch Aisyiyah Makamhaji established a charity to foster harmonious family and Islamic sermon on Â 9th of each month and islamic sermon held in each branch Aisyiyah Makamhaji.